2022
DOI: 10.1177/10499091221123049
|View full text |Cite
|
Sign up to set email alerts
|

Is Weight Loss During Chemotherapy for Pancreatic Cancer Prognostic?

Abstract: Background Predicting poor survival outcomes early in palliative chemotherapy is important to the timing of palliative care. Weight loss during chemotherapy if prognostic would lead to early palliative care. Method We collected demographics, stage, chemotherapy, chemotherapy cycles, weight, healthcare utilization, comorbidities (Charleson Comorbid Index), tumor markers, and weight changes over 60 days. We defined 3 groups of patients: 1. Weight gain to <.5% weight loss, 2. Weight loss< 2% and 3. Weight l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
2
2
0
Order By: Relevance
“…Recollection of weight data after months is reported to be less reliable 28 . A previous study conducted in patients with pancreatic cancer suggests that postdiagnosis weight loss over 60 days did not predict poor prognosis 32 . Because we also employed a short time frame, these results support the superiority of our timing strategy in this study.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Recollection of weight data after months is reported to be less reliable 28 . A previous study conducted in patients with pancreatic cancer suggests that postdiagnosis weight loss over 60 days did not predict poor prognosis 32 . Because we also employed a short time frame, these results support the superiority of our timing strategy in this study.…”
Section: Discussionsupporting
confidence: 77%
“… 28 A previous study conducted in patients with pancreatic cancer suggests that postdiagnosis weight loss over 60 days did not predict poor prognosis. 32 Because we also employed a short time frame, these results support the superiority of our timing strategy in this study. Future studies need to explore the prognostic significance of more weight change time frames that vary in length and timing.…”
Section: Discussionsupporting
confidence: 70%
“…There seems to be no consensus among different studies on how weight change affects the prognosis of PC. (19)(20)(21) The conclusion of the effect of skeletal muscle on the prognosis of PC seems to be more consistent. (22)(23)(24)(25) In our study, skeletal muscle change was identi ed as a prognostic factor in PFS nomograms by LASSO Cox regression analysis, whereas weight change only showed borderline signi cance in the nal model of OS.…”
Section: Disscusionmentioning
confidence: 87%
“…Davis et al retrospectively reported that weight loss over 60 days during chemotherapy, but not at diagnosis, did not predict a poor prognosis in 93 patients with PC. 18 On the other hand, Yildirim et al reported that a weight loss of 3.1% during chemoradiotherapy was an independent predictor of poor survival in 73 patients with locally advanced PC treated with chemoradiotherapy. 19 These conflicting results suggest that weight loss and survival may result from multiple factors.…”
Section: Discussionmentioning
confidence: 99%